S3440P Substitution in C-Terminal Region of Human Reelin Dramatically Impairs Secretion of Reelin from HEK 293T cells - Esmaeilzadeh-Gharehdaghi, Elika; Razmara, Ehsan; Bitaraf, Amirreza; Mahmoudi, Mahdi; Garshasbi, Masoud (Cellular and Molecular Biology, 2019)
Reelin is a large extracellular glycoprotein secreted by Cajal–Retzius cells and has a main role during brain development, especially in neuronal migration. Reelin is comprised of N-terminal F-Spondin like domain, eight tandem repeats, and a highly conserved basic C-Terminal Region (CTR). The CTR main role in the secretion of Reelin has been investigated by advertently inducing deletion in whole or a part of this region; however, the role of CTR point mutations on the secretion of Reelin is shrouded in mystery. In this study, we performed experimental analyses on a sub-region of Human Reelin containing 5th and 6th repeats (R5-R6), a part of 8th repeat and the CTR which were amplified from cDNA of K562 and HEPG2(HepatocellularG2) cells and cloned into a mammalian expressional plasmid (pVP22/myc-His). Bioinformatics investigation was performed on the CTR at both level of nucleotide and amino acid as well as mutant type. Random mutagenesis by error-prone PCR method was utilized to induce mutation in the CTR. The secretion efficiency of recombinant wild-type and mutant Reelin constructs compared in cell lysate and supernatant isolated from the transiently transfected HEK 293T cells using 6XHistag ELISA method. In-vitro study demonstrated that the CTR alteration (S3440P) leads to impairment of Reelin secretion even after overexpression. Our results indicate that S3440P substitution is the highly conserved structure of the CTR has an important effect on Reelin secretion.